Comammox Nitrospira play a minor role in N2O emissions from an alkaline arable soil. (August 2022) - Tan, Che; Yin, Chang; Li, Wenjuan; Fan, Xiaoping; Jiang, Yishun; Liang, Yongchao
Abstract: Nitrogen addition to croplands greatly increases global emissions of the potent greenhouse gas nitrous oxide (N2 O). Three ammonia-oxidizing functional guilds constitute the major producers of N2 O in agricultural soils, but their relative contributions are still poorly understood, especially the newly discovered and widespread complete ammonia oxidizers (comammox). To fill this knowledge gap, we used three nitrification inhibitors: acetylene, 1-octyne, and 3, 4-dimethylpyrazole phosphate (DMPP), to selectively suppress the activity of different ammonia oxidizer guilds to discriminate their relative contributions to N2 O production in an alkaline arable soil. The results indicated that DMPP completely inhibited the growth of comammox Nitrospira clade A and ammonia-oxidizing bacteria (AOB) but promoted ammonia-oxidizing archaea (AOA) growth, while the abundance of comammox Nitrospira clade A increased in the presence of 1-octyne at high ammonium (NH4 + ) concentrations. AOB dominated N2 O production in soils with inorganic NH4 + amendment, followed by AOA, while comammox Nitrospira contributed to less than 3% of total N2 O emissions with an N2 O yield of ∼0.083% (N2 O per molecule of nitrate). The abundance of comammox Nitrospira clade A was approximately two orders of magnitude lower than that of canonical ammonia-oxidizers. Phylogenetic analysis revealed that the majority of comammox Nitrospira clade A belonged to a new cluster that was separated from the known comammox bacterium. Taken together, our results clearly and strongly demonstrate that comammox Nitrospira play only a minor role in N2 O emissions in a heavily fertilized alkaline arable soil. Highlights: Comammox Nitrospira only contributed to less than 3% of total N2 O emissions from a heavily fertilized arable soil. DMPP inhibited the growth of AOB and comammox Nitrospira clade A, but 1-octyne only inhibited the growth of AOB. The growth of AOA was further increased when both AOB and comammox Nitrospira clade A were inhibited.